ASEPTIC NECROSIS OF FEMORAL HEAD IN PATIENT AFTER VIRAL INFECTION, TREATED FOR A HERNIATED DISC - Gergana Gecheva-Fermendzhieva (Journal of IMAB)
This case presents a patient with severely painful and limited gait when he was addmitted to the Department of Physical and Rehabilitation medicine. The complains of limited gate and pain in the area of hips gradually increased over a year after a severe viral infection that was treated with corticosteroids. At the beginning the complaints were in the lower back area which is why the patient underwent an MRI of the lower back where changes in the intervertebral discs were detected. The patient began a treatment for herniated disk which had a temporary and insufficient effect. When admitted to the Department, X-Ray images of hips were taken and the patient was diagnosed with aseptic necrosis of the hip's head known as Morbus Chandler. The case presents a successful rehabilitation due to correct diagnosis, made before beginning any rehabilitation and subsequently referring the patient for surgical treatment Aim. The aim is to highlight the importance of correct diagnosis for successful rehabilitation of aseptic necrosis of the hip joints. Materials and methods: One 68-yaers male was included in this study. X-RAY of pelvis and MRI of lumbar area were performed. Neurological and orthopedic examination and gait assessment were performed. Result: The patient was correctly diagnosed and referred to surgical treatment. Intensive rehabilitation and kinesiotherapy were performed, which restored the patient's general condition and improved his gait. Conclusion: We consider it necessary to recall that the symptoms of a herniated disc and hip joint diseases overlap in most cases and it is of utmost importance in differential diagnosis to distinguish. A pelvic X-ray or hip MRI is necessary to make the diagnosis and differentiation.